Social Media and Women Empowerment: A Digital Feminist Analysis of “Watch Us Rise” by Watson and Hagan (Journal of Social Sciences Review, 2022)
This research study aims to explore the role of digital media in women empowerment in the  context of Watson and Hagan’s novel Watch Us Rise (2019) by keeping in view Mendes,  Ringrose and Keller’s work Digital Feminist Activism (2019) as a model framework. This study finds out different ongoing aspects of digital feminism and efforts of young feminist activists for women’s rights. Mendes, Ringrose and Keller (2019) claim that young feminist activists are using digital media as a platform to fight against rape culture by using different hashtags. This research study aims to find out different opinions and feelings of feminists regarding digital feminism. In this particular research study, it is described that Watson and Hagan (2019) have also used different hashtags in their work which are labeling Watch Us Rise (2019) a digital feminist text. In order to determine the role of digital media in women empowerment, Watson and Hagan’s (2019) work has been analyzed from digital feministic perspective. The findings of the research reveal that digital media is empowering women by providing them digital space and online support.
Keywords: Feminism; Digital Media; Women Empowerment; Rape Culture; Misogyny; Hashtag Feminism; Intersectionality; Racism